Back to a new normal : in search of stability in an era of pandemic disruption - insight from practitioners and academics - Malka, S. Charles; Tiell, Robert H. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"This book aims at exploring the profound effects of Covid-19 on people's ways of life at home and at work, and offers strategies and expert advice for 'survival' as the world finds itself in a new reality that has formed by the pandemic. At the very core of Back to a New Normal is the premise that the virus, which continues to infect more than 137 million individuals worldwide and has caused more than 3.5 million deaths, has also triggered radical changes within individual and organizational levels. At the same time, it opened opportunities that ignited human ingenuity and tested human adaptation. Taming the pandemic is urgent and essential but it is just the first step. Just as critical, is the need to be better prepared for future pandemics that are sure to occur. Focusing primarily on the later, the book's chapters follow a how to approach by exposing the severity of Covid-19's impact on the behaviors of people and organizations, and effective ways for managing the pandemic's unfolding consequences with an eye on the future. For that purpose, we asked a group of experts from the academia and practitioners from various fields to share their know how and experience dealing with the consequences of the pandemic, and offer strategies for coping with its harmful effects. This book follows in that vein"--